ANALISIS KUALITAS PELAYANAN, HARGA BERPENGARUH TERHADAP KEPUASAN PELANGGAN YANG BERDAMPAK PADA LOYALITAS PELANGGAN (Kasus Pada Pelanggan CV. Nur Angkasa - Banyuwangi) - Nurul Hidayah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2016)
Loyal customers are very important to the enterprisesbecause of the cost to acquire new customers is more expensivethan keeping old customers. Variable in this research is thequality of service, price, and customer satisfaction that isassumed to be able to increase the positive impact against theloyalty of consumers. This research is associative research tofind out the relationship between two or more variables. Thepopulation in this research is the consumer CV Nur Angkasa JL.KH. Hasan, RT 03 RW., 2, Tegalarum-Sempu, Banyuwangi. Thesample in this research are consumer CV. Nur Angkasa as muchas 148 consumers. Data analysis in this research was done in adescriptive. The research results proved that the quality ofservice and price have give a positive and significant effectagainst the satisfaction and loyalty of customers. Customersatisfaction have give a positive influence not significantly tocustomer loyalty.